Anti-skin aging effect of centella asiatica and cosmos caudatus extracts / Ku Fatin Nurdiana Ku Fairos Nizam - Ku Fairos Nizam, Ku Fatin Nurdiana (2022)
Many scientific studies have demonstrated the anti-skin aging effects of Centella asiatica and Cosmos caudatus extracts. Skin aging is defined as the changes in the skin, structurally and functionally, due to aging. Reactive oxygen species (ROS) is central in skin aging and we hypothesized that neutralizing ROS may be the key in combating aging. Natural-based compounds are becoming essential in skincare industry as chemical or synthetic compounds may cause adverse effects. Centella asiatica, which has a lot of bioactive compounds such as flavonoids and madecassoside, can be utilized as an antiaging ingredient to moisturize smooth, and soothe the skin. Similarly, Cosmos caudatus also acts as an antiaging agent as it contains several bioactive compounds that are potent antioxidants such as proanthocyanidins. Due to their high antioxidant activities, it was hypothesized that these extracts possess antiaging activity. In these experiments, Centella asiatica and Cosmos caudatus extracts were tested for diphenyl-picrylhydrazyl (DPPH) radical scavenging activity and for tyrosinase inhibition action. Centella asiatica extract exhibited 62.00% of DPPH radical scavenging activity at 0.15 mg/ml while Cosmos caudatus extract exhibited 69.72% of DPPH radical scavenging activity at 0.15 mg/ml. IC50 value of Cosmos caudatus activity was determined to be 0.018 mg/ml and the IC50 value of Centella asiatica at 0.012 mg/ml. Centella asiatica inhibited 29.97% activity of tyrosinase activity whereas Cosmos caudatus inhibited 40.91% tyrosinase activity. Both extracts showed significant antioxidant and anti-tyrosinase activities. Based on these findings, the hypothesis is accepted as both extracts exhibit DPPH scavenging activity and anti-tyrosinase activity. However, the causal relationship between these two activities still requires further studies. Nonetheless, both extracts show promising results and may be further developed into safe and efficacious skincare products.